P16.03.A Epithelioid gliobastoma requires rapid treatment and BRAF inhibitors should be made readily available for their treatment. (5th September 2022) - Hurwitz, V; La, J; Lavrador, J; Brazil, L; Chia, K; Swampillai, A; Al-Salihi, O; Bhangoo, R; Vergani, F; Ashkan, K; Hedges, S; Kostick, E; et al.
Abstract: Background: Epithelioid glioblastoma is a rare subtype of Glioblastoma. We examine two cases who presented acutely with symptoms of headache, neck stiffness and an eye squint. The purpose of this case review is to look at their management, the spread of the disease and propose the availability of BRAF inhibiting agents be made readily available for this subtype. Material and Methods: The clinical records including pathology and surgical reports, multi-disciplinary team meeting documents, oncology plans and inpatient notes have all been reviewed alongside the literature on epithelioid GBM and BRAF V600e mutations and inhibitors. Results: Patients were females aged 25 and 32 presenting with acute onset headache and neck stiffness to emergency Department. The 25 year old had developed a right eye squint within seven days of the other symptoms, her tumour was right frontal with midline shift. The 32 year old had symptoms for 10 days prior to presentation, the tumour was right temporal. They both underwent craniotomies. The frontal tumour was totally resected, while the temporal lobe tumour was haemorrhagic in nature and minimally de-bulked. Pre-operative stealth imaging showed that there had been an increase in the size of the temporal lesion in the fourteen days since presentation. Histology proved these to be epithelioid GBM's with BRAF V600e mutations, IDH wild-type and TERT promoter mutant. Full pathology reports with molecular markers were available within ten days. The frontal lobe patient began chemo-radiation sixteen days from her surgical date. On day two she was admitted with severe headache and nausea. She became agitated, confused, and transferred back to the neurosurgery unit for management of hydrocephalus. She was diagnosed with PRES and simultaneously treated for this and hydrocephalus. Clinically she suffered storming, passing away exactly eight weeks from presentation. Seven days after surgery the temporal lobe tumour patient suffered a seizure and admitted for symptom management and expedite oncology treatment. She passed away six days later suffering continual neurological deterioration and the tumour progression with leptomeningeal spread. This was exactly four weeks from initial presentation. Conclusion: The prognosis for epithelioid Glioblastoma is limited to weeks to short months. Extent of resection in these case studies demonstrates benefit in delaying progression though it is clear that time is of the essence from presentation, to surgery, to adjuvant treatment. Neither of these tumours were methylated meaning the standard treatment for glioblastoma is likely to lack efficacy. BRAF inhibitors should be made readily available for this rare sub-type to commence treatment expediently. Both patients suffered distressing neurological symptoms in their final days which require expert management and are best managed in a neurosurgical centre.